Clinical development of anti‐CD19 chimeric antigen receptor T‐cell therapy for B‐cell non‐Hodgkin lymphoma - Makita, Shinichi (Cancer Sci, 2017)
B‐cell non‐Hodgkin lymphoma (B‐NHL) is the most frequent hematological malignancy. Although refined chemotherapy regimens and several new therapeutics including rituximab, a chimeric anti‐CD20 monoclonal antibody, have improved its prognosis in recent decades, there are still a substantial number of patients with chemorefractory B‐NHL. Anti‐CD19 chimeric antigen receptor (CAR) T‐cell therapy is expected to be an effective adoptive cell treatment and has the potential to overcome the chemorefractoriness of B‐cell leukemia and lymphoma. Recently, several clinical trials have shown remarkable efficacy of anti‐CD19 CAR T‐cell therapy, not only in B‐acute lymphoblastic leukemia but also in B‐NHL. Nonetheless, there are several challenges to overcome before introduction into clinical practice, such as: (i) further refinement of the manufacturing process, (ii) further improvement of efficacy, (iii) finding the optimal infusion cell dose, (iv) optimization of lymphocyte‐depleting chemotherapy, (v) identification of the best CAR structure, and (vi) optimization of toxicity management including cytokine release syndrome, neurologic toxicity, and on‐target off‐tumor toxicity. Several ways to solve these problems are currently under study. In this review, we describe the updated clinical data regarding anti‐CD19 CAR T‐cell therapy, with a focus on B‐NHL, and discuss the clinical implications and perspectives of CAR T‐cell therapy.